Cerebral laterality and body composition in judo athletes - Akalin, Tevfik Cem (Progress in Nutrition, 2020)
Study Objectives: In this study, it was aimed to determine cerebral lateralization and functional asymmetry of the brain not only by adhering to hand preference, but also with the relation of the foot, eye, ear preferences, and somatotype. Methods: The sample was composed of 120 athletes (79 males and 41 females) who had participated in the Turkish Judo Championship. Their mean age and training experiences were 21.05 years (range 18–26) and 9.61 years (range 3-18) respectively. Hand preference was assessed using the Edinburgh Handedness Inventory. Some questions were asked to the subjects in the questionnaires in order to evaluate the range of preferences about a foot, eye, and ear. The hand grip strength measurements were made via the Jamar hydraulic hand dynamometer. Total body fat percentage was estimated by single-frequency, 8 electrodes bioelectric impedance analyzer system (BC-418, Tanita Corp, Tokyo, Japan). The components of somatotype were calculated according to the Heath-Carter technique. Data were collected, to SPSS program and Independent Samples T-test and Chi-Square test was used for the analysis of the obtained data. Analysis results were evaluated in the %95 confidence interval. Results: When the distribution of hand preference of the subjects (n= 120) was considered, 87,5% (n= 105) of the subjects preferred the right hand and 12,5% (n= 15) of the subjects preferred the left hand. Somatotype features of judo athletes were determined as the generally mesomorph. Conclusion: The results show that there was a difference between the dominant hand and the preferred foot, eye, and ear, and it is predicted that it can be reliable in all four preferences in determining the cerebral hemispheres. Despite that, according to the dominant hand preferences in judokas, there were no difference between BMI, body fat percentages, and somatotype features.